Brucea javanica Oil Emulsion Promotes Autophagy in Ovarian Cancer Cells Through the miR-8485/LAMTOR3/mTOR/ATG13 Signaling Axis - Wang, Yihan; Chen, Bocen; Xiao, Man; Wang, Xiaoli; Peng, Yunhua (Frontiers in Pharmacology, 2022)
Ovarian cancer is a common malignant tumor of female reproductive tract, with the highest mortality rate. Currently, there are no effective approaches to improve the survival rate. Brucea Javanica Oil Emulsion (BJOE), an extract from Brucea javanica (L.) Merr. [Simaroubaceae], has anti-tumor effects and can increase the sensitivity of radiotherapy and chemotherapy in many types of cancers. MiR-8485, a discovered miRNA, has been shown to be involved in the occurrence and development of tumors. The purpose of this study was to investigate the effect of BJOE on the regulation of mammalian rapamycin target protein (mTOR) autophagy signal pathway and related autophagy factors on ovarian cancer cells through miR-8485. The qRT-PCR results showed that the expression of miR-8485 increased after BJOE treatment in SKOV3 cell. The CCK8 assay and flow cytometry analysis revealed that both BJOE and miR-8485 overexpression inhibited the proliferation and promoted the apoptosis of SKOV3 cell. MDC fluorescence staining showed that BJOE and miR8485 overexpression led to a significant increase in autophagy vesicles in SKOV3 cell. Double luciferase reporter assay confirmed the existence of binding sites between miR8485 and LAMTOR3. The results of qRT-PCR and western blot showed that BJOE and overexpressed miR-8485 down-regulated the expression of LAMTOR3 and mTOR, and up-regulated the expression of ATG13 and LC3-Ⅱ.Conclusion: 1. MiR-8485 may be the key factor of BJOE in promoting autophagy and apoptosis and inhibiting cell proliferation of ovarian cancer cells; 2. BJOE may play an anti-tumor role by regulating LAMTOR3 / mTOR / ATG13 signaling axis through miR-8485 to promote autophagy in ovarian cancer cells.